La lecture/déchiffrement en Algérie et la méthode syllabique - Afaf Salhi; Mourad Bektache (Multilinguales)
Through this study, we raise the problem of the impact of the syllabic method on the performance of Algerian third-year primary-school learners in terms of reading/deciphering skills. Our research design is based on an experiment conducted with fifteen third-year classes in nine primary schools situated in the f2 district of the wilaya of Constantine. The results will indicate to what extent the contribution of the application of such an approach would be in favor of a good mastery of the reading activity. A questionnaire intended for teachers would allow us to evaluate the adequacy of the methodological principles of this method with in different working conditions.